Pengaruh Trust, Commitment, Communication Dan Conflict Handling Terhadap Customer Loyalty Nasabah Tabungan Pt Bank Panin Tbk Di Jakarta - Ollie Marcella (Universitas Tarumanagara, 2019)
The purposes of this study are : First, to explore the effect among trust on customer loyalty. Second, to explore the effect among commitment on customer loyalty. Third, to explore the effect among communication on customer loyalty. Fourth, to explore the effect among conflict handling on customer loyalty. The population of this research are all customers of PT Bank Panin Tbk savings in Jakarta. The Samples are collected from PT Bank Panin Tbk's savings customers in South Jakarta. The method of data collection is cross-sectional design with 150 respondents. The technique of data analysis used in this study was multiple regression analysis. The results are : (a) trust has a positive effect toward customer loyalty; (b) commitment has not positive effect toward customer loyalty; (c) communication has a positive effect toward customer loyalty; (d) conflict handling has a positive effect on customer loyalty.